Evolutionary Dynamics of Coordinated Cooperation - Ohtsuki, Hisashi (Frontiers in Ecology and Evolution, 2018)
In social evolution theory, unconditional cooperation has been seen as an evolutionarily unsuccessful strategy unless there is a mechanism that promotes positive assortment between like individuals. One such example is kin selection, where individuals sharing common ancestry and therefore having the same strategy are more likely to interact with each other. Conditional cooperation, on the other hand, can be successful if interactions with the same partners last long. In many previous models, it has been assumed that individuals act conditionally on the past behavior of others. Here I propose a new model of conditional cooperation, namely the model of coordinated cooperation. Coordinated cooperation means that there is a negotiation before an actual game is played, and that each individual can flexibly change their decision, either to cooperation or to defection, according to the number of those who show the intention of cooperation/defection. A notable feature of my model is that individuals play an actual game only once but can still use conditional strategies. Since such a negotiation is cognitively demanding, the target of my model here is exclusively human behavior. I have analyzed \revise{cultural} evolutionary dynamics of conditional strategies in this framework. Results for an infinitely large population show that conditional cooperation not only works as a catalyst for the evolution of cooperation, but sustains a polymorphic attractor with unconditional cooperators, unconditional defectors, and conditional cooperators being present. A finite population analysis is also performed. Overall, my results provide one explanation of why people tend to take into account others' decisions even when doing so gives them no payoff consequences at all.